2019
DOI: 10.3390/cells8050381
|View full text |Cite
|
Sign up to set email alerts
|

Telomere Length and Risk of Major Adverse Cardiac Events and Cancer in Obstructive Sleep Apnea Patients

Abstract: Telomere length (TL) is associated with cardiovascular disease (CVD) and cancer. Obstructive sleep apnea (OSA) is also linked to higher risk of CVD and cancer, and to TL. We investigated the association between TL and risk of major adverse cardiac events (MACE) and cancer in OSA patients. We studied 210 individuals undergoing sleep-related studies between 2000 and 2007. Baseline characteristics and follow-up data (available in 164 subjects) were obtained from clinic records. Incidence rates were calculated for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 53 publications
0
14
0
Order By: Relevance
“…Particularly, in OSA patients, sleep stability significantly decreased with reduced TL (AHI ≥ 15) ( Kwon et al, 2015 ). Polonis et al (2019) reported that OSA patients had a higher likelihood of cancer but no clear evidence of an elevated incidence of major adverse cardiac events and no association with TL or cancer risk.…”
Section: Resultsmentioning
confidence: 95%
“…Particularly, in OSA patients, sleep stability significantly decreased with reduced TL (AHI ≥ 15) ( Kwon et al, 2015 ). Polonis et al (2019) reported that OSA patients had a higher likelihood of cancer but no clear evidence of an elevated incidence of major adverse cardiac events and no association with TL or cancer risk.…”
Section: Resultsmentioning
confidence: 95%
“…Telomere expression signatures were chosen because mean telomere length in blood cells is associated with lifestyle and disease characteristics. In human leukocytes it negatively correlates with lifespan and BMI (Rode et al, 2015 ; Gielen et al, 2018 ) and it associates with heart diseases, type 2 diabetes, cancer (Oeseburg et al, 2010 ; Haycock et al, 2014 ; Polonis et al, 2019 ), lifestyle factors (Townsend et al, 2016 ), diet (Leung et al, 2018 ), and psychological stress (Epel and Prather, 2018 ). Hence, we are interested whether genes with telomere functions activate differently in the transcriptomic types or not.…”
Section: Resultsmentioning
confidence: 99%
“…The data on the association between TL and OSA are contradictory. Many studies have reported LTL shortening in OSA [ 59 , 60 , 61 , 62 , 63 ]; however, a few studies have reported telomere lengthening [ 64 , 65 , 66 ].…”
Section: Discussionmentioning
confidence: 99%